Incomplete stent expansion in flow‐diversion treatment affects aneurysmal haemodynamics: a quantitative comparison of treatments affected by different severities of malapposition occurring in different segments of the parent artery. (17th June 2021) - Zhang, Mingzi; Li, Yujie; Sugiyama, Shin‐ichiro; Verrelli, David I.; Matsumoto, Yasushi; Tominaga, Teiji; Qian, Yi; Tupin, Simon; Anzai, Hitomi; Ohta, Makoto
Abstract: Incomplete stent expansion (IncSE) is occasionally seen in flow‐diversion (FD) treatment of intracranial aneurysms; however, its haemodynamic consequences remain inconclusive. Through a parametric study, we quantify the aneurysmal haemodynamics subject to different severities of IncSE occurring in different portions of the stent. Two patient cases with IncSE confirmed in vivo were studied. To investigate a wider variety of IncSE scenarios, we modelled IncSE at two severity levels respectively located in the proximal, central, or distal segment of a stent, yielding a total of 14 treatment scenarios (including the ideal deployment). We examined stent wire configurations in 14 scenarios and resolved aneurysm haemodynamics through computational fluid dynamics (CFD). A considerable degradation of aneurysm flow‐reduction performance was observed when central or distal IncSE occurred, with the maximal elevations of the inflow rate (IR) and energy loss (EL) being 10% and 15%. The underlying mechanism might be the increased resistance for flow to remain within the FD stent, which forces more blood to leak into the aneurysm sac. Counter‐intuitively, a slight reduction of aneurysm inflow was associated with proximal IncSE, with the maximal further reduction of the IR and EL being 5% and 8%. This may be due to the disruption of the predominant parent‐artery flow by the collapsed wires, which decreased the strength and altered the direction of aneurysmal inflow. The effects of IncSE vary greatly with the location of occurrence, revealing the importance of performing individualised, patient‐specific risk assessment before treatment. Abstract : We reproduced a series of incomplete stent expansion (IncSE) scenarios in two patients and successfully compared the collapsed wire structures against those observed in DSA images. Quantification of the post‐treatment aneurysmal haemodynamics suggests that effects of IncSE vary greatly with the location of occurrence, from potentially causing a slight aneurysm inflow reduction to causing a severe deterioration in flow‐diversion performance. The collapsed stent wires may alter the predominant flow direction and increase resistance to flow remaining within the stent lumen. ​